The wisdom of Morrie : living and aging creatively and joyfully - Schwartz, Morrie; Schwartz, Rob (United States: Blackstone Publishing, 2023)
From the eponymous subject of the beloved classic Tuesdays with Morrie comes an insightful, poignant masterpiece on staying vibrant and connected for life.
Keywords: Schwartz, Morriz S; Adjustment (Psychology); Aging; Amyotrophic lateral sclerosis -- Patients -- United States -- Biography; Conduct of life; Terminally ill -- Psychology; Self-help publications